Women, Culture and Africa’s Land Reform Agenda - Akinola, Adeoye O. (Frontiers in Psychology, 2018)
Pre-colonial Africa pride itself on adherence to diverse cultural affinity and traditional belief system, which defines the place of women in respect to land access, use and ownership. Land resource continues to play important roles in both agrarian and industrial societies; thus, absence of effective land management and gender construction in land allocations has deepened gender inequality, restricted women’s capacity building and agricultural development in Africa. This article explores the impact of African traditional practices and cultural beliefs on women’s land ownership and use, it also reconciles women’s land rights (access and control) with the realities of land reform in post-colonial Africa. It explores how gender inequalities, in terms of land ownership and rights, have jeopardized attempts at agricultural productivity and sustainable development in Africa. Although, it is tasking to ‘universalize’ Africa culture and locate it in a centre, due to the diverse cultural values found in Africa. However, there are certain belief systems that run through most African communities, such as the denials of women’s land rights and patriarchal nature of the societies. Thus, the article found that, despite the development of legal frameworks that expands women’s property rights, cases of cultural impediments to the exercise of land rights abound in Africa. Key words: Culture, Women rights, Land Reform, Land Labour, Human capacity building, Africa.